ORGANIZATION OF ACCOUNTING IN SMALL ENTERPRISES - PRACTICE OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2021)
This article discusses the features of the organization of accounting in small enterprises operating in the Republic of Uzbekistan. At the same time Necessary suggestions and recommendations were given to improve the efficiency of accounting at small enterprises.